Classification for Longevity Potential: The Use of Novel Biomarkers - Beekman, Marian; Uh, Hae-Won; van Heemst, Diana; Wuhrer, Manfred; Ruhaak, L. Renee; Gonzalez-Covarrubias, Vanessa; Hankemeier, Thomas; Houwing-Duistermaat, Jeanine J.; Slagboom, P. Eline (Frontiers in Public Health, 2016)
Background: In older people chronological age may not be the best predictor of residual lifespan and mortality, because with age the heterogeneity in health is increasing. Biomarkers for biological age and residual lifespan are being developed to predict disease and mortality better at an individual level than chronological age. In the current paper we aim to classify a group of older people into those with longevity potential or controls. Methods: In the Leiden Longevity Study participated 1671 offspring of nonagenarian siblings, as the group with longevity potential, and 744 similarly aged controls. Using known risk factors for cardiovascular disease, previously reported markers for human longevity and other physiological measures as predictors, classification models for longevity potential were constructed with multiple logistic regression of the offspring-control status. Results: The Framingham Risk Score is predictive for longevity potential (AUC = 64.7). Physiological parameters involved in immune responses and glucose, lipid and energy metabolism further improve the prediction performance for longevity potential (AUCmale = 71.4, AUCfemale = 68.7). Conclusion: Using the Framingham Risk Score, the classification of older people in groups with longevity potential and controls is moderate, but can be improved to a reasonably good classification in combination with markers of immune response, glucose, lipid and energy metabolism. We show that individual classification of older people for longevity potential may be feasible using biomarkers from a wide variety of different biological processes.